Analytical review on common and state-of-the-art FR strategies for VSC-MTDC integrated offshore wind power plants. (September 2021) - Khan, Asif; Seyedmahmoudian, Mehdi; Raza, Ali; Stojcevski, Alex
Abstract: With the unprecedented growth in recent voltage source converter-based high voltage direct current (VSC-HVDC) integrated offshore wind power plants, frequency regulation of onshore systems and their stability has been crucial. Offshore wind farms cannot directly provide frequency support to the onshore AC grid as back-to-back converters in variable speed wind turbines and HVDC grid decouple the two ending terminals. It prevents the kinetic and electrostatic energy from mitigating the frequency transients in the onshore AC grid. Low inertia contributes to an increase in the rate of change of frequency with a further decrease in frequency nadir that undermines the onshore AC system's reliability. However, variable speed wind turbines and voltage source converter stations with appropriate control strategies can efficiently participate in the onshore AC grid's frequency regulation. This paper provides an in-depth review of the frequency support strategies for offshore wind power plants and the voltage source converter stations in a multi-terminal HVDC system, including a comparison of the related approaches and the potential gaps present in the existing literature. This paper also provides guidelines and serves as a reference for researchers focused on the frequency support strategies for such an integrated system. Highlights: A comprehensive review on power system frequency regulation through VSWTs and VSC stations is presented. SFD occurs during rotor speed recovery if no other power is available to compensate for power shortage at that moment. Use of ESS could be a viable alternative to compensate for the energy shortage during rotor speed recovery. AFC-based coordinated control in VSC-HVDC is the preferred practicing technology due to its simplicity and robustness. New protocols need to be defined to cyber secure the offshore wind power plant-based power systems.